2005
DOI: 10.1038/sj.cdd.4401790
|View full text |Cite
|
Sign up to set email alerts
|

JNK pathway mediates apoptotic cell death induced by tumor suppressor LKB1 in Drosophila

Abstract: Although recent progresses have unveiled the diverse in vivo functions of LKB1, detailed molecular mechanisms governing these processes still remain enigmatic. Here, we showed that Drosophila LKB1 negatively regulates organ growth by caspase-dependent apoptosis, without affecting cell size and cell cycle progression. Through genetic screening for LKB1 modifiers, we discovered the JNK pathway as a novel component of LKB1 signaling; the JNK pathway was activated by LKB1 and mediated the LKB1-dependent apoptosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…miR-26a decreases expression of the tumor suppressors PTEN and RB1 and inhibits expression of MAP3K2/MEKK2, an activator of c-Jun N-terminal kinase (JNK) (12). JNK has also been implicated in tumor suppression (13). In this manner, miR-26a transforms NIH 3T3 cells and cooperates with CDK4 and CENTG1 to increase GBM growth.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…miR-26a decreases expression of the tumor suppressors PTEN and RB1 and inhibits expression of MAP3K2/MEKK2, an activator of c-Jun N-terminal kinase (JNK) (12). JNK has also been implicated in tumor suppression (13). In this manner, miR-26a transforms NIH 3T3 cells and cooperates with CDK4 and CENTG1 to increase GBM growth.…”
mentioning
confidence: 95%
“…We also identified MAP3K2/MEKK2, an activator of the JNK pathway, which has been implicated in apoptosis and tumor suppression (13,19). Thus, PTEN, RB1, and MAP3K2/MEKK2 were chosen for further study.…”
mentioning
confidence: 99%
“…Mutant larvae can survive up to early pupal stages and exhibit overgrowth of the central nervous system (CNS) at the white prepupal stage (Fig. 1 C-E), as described previously (65). To analyze the brain overgrowth phenotype in more detail, we quantified the volume of the VNC and OL compartments separately.…”
Section: Significancementioning
confidence: 99%
“…29 Additionally, some studies found that JNK is another potent downstream kinase, which accounts for LKB1- induced apoptosis. 30 JNK can initiate cytochrome c release to mediate mitochondrial apoptosis signaling pathway, which is an essential procedure of cisplatin-mediated cell apoptosis. 31 These studies assume that LKB1-enhancing cisplatin-mediated NSCLC cell apoptosis may be partly through p53-and JNK-related signaling pathways.…”
Section: Discussionmentioning
confidence: 99%